Chikungunya chronic disease: a systematic review and meta-analysis. (11th July 2018) - Paixão, Enny S; Rodrigues, Laura C; Costa, Maria da Conceição N; Itaparica, Martha; Barreto, Florisneide; Gérardin, Patrick; Teixeira, Maria Glória
Abstract: Background: Chikungunya is a mosquito-borne disease caused by an arthritogenic alphavirus, with four genotypes: East Central South African (ECSA), West African, ECSA-diverged or Indian Ocean Lineage (IOL) and Asian lineage. Overall, the disease is self-limited; however, in some patients, joint pain and other non-specific symptoms can last for months or years. This systematic review and meta-analysis aims to estimate the proportion of people that self-report chikungunya-related chronic non-specific symptoms. Methods: Medline, EMBASE, Global Health Library and Scopus were searched for articles published before March 2017. Case-control, cohort, cross-sectional, clinical trials studies and outcome-independent case series were eligible. It was estimated that the proportion of patients who did not recover, by virus genotype, and by the time between disease onset and assessment of chronic symptoms. Results: A total of 38 studies were included in the review and 34 in the meta-analysis. Of 6532 chikungunya patients, 3157 did not recover fully after 3 months. The overall no recovery rate associated with chikungunya was 43% (95% CI, 35–52%); Inter-genotype group heterogeneity was observed, the highest prevalence in the ECSA-diverged genotype: 50% (95% CI; 40–60%), followed by the Asian lineage genotype: 36% (95% CI; 20–52%). After 12 months follow-up, the overall no-recovery rate was 21% (95% CI; 19–22%). Conclusion: The evidence suggests that the prevalence of chronic discomfort associated with chikungunya illness varies by virus lineage. The proportion of people that do not fully recovered after chikungunya was high and, therefore, health authorities must prepare to treat patients with symptoms of long-lasting chikungunya adequately addressing the physical, psychological and social needs.